Current Issues in Teacher Autonomy - Wiśniewska, Danuta (Glottodidactica, 2007)
This paper provides a review of a selection of the literature in the field of English foreign language teaching related to teacher autonomy. The focus is on the core themes recurring in the literature, which comprise: rationale for teacher autonomy, definitions of the concept, descriptions of an autonomous teacher, recognition of the constraints on autonomy and suggestions for teacher education promoting teacher autonomy.